High-Quality Legal Education as a Source for the Formation of Legal Culture and Professional Legal Awareness of Lawyers - Anatolyevna Sergeeva, Anzhelika; Anatolyevna Gorbatova, Marina; Gennadevich Rusetskiy, Mikhail; Sergeevna Tikhonova, Svetlana; Alekseevna Efremova, Irina (Opción, 2019)
The article considers higher legal education as a source for the formation of legal culture, as well as professional legal awareness of lawyers as a structu- ral element of legal culture. The reasons that give rise to legal nihilism among lawyers are analyzed. The authors particularly highlight the shortco- mings and omissions in the process of legal training and education of future lawyers. Special attention is paid to the characteristics of the educational environment in higher education institutions in Russia, which provide training for legal personnel, including the requirements that the state sets to the quality of legal education in Russia, as well as the compliance of higher education institutions with these requirements. It is concluded that profes- sional competency of a lawyer should be formed simultaneously with gene- ral cultural competency, which, in turn, is characterized by respect for the law, as well as a strong belief in the need for professional activity to adhere to the norms of morality and demonstrate lawfully oriented behavior.